DIFFERENTIATION STRATEGY TO INCREASE THE LOAD FACTOROF LRT SUMSEL THROUGH THE IMPLEMENTATION OF A TRANSITORIENTED DEVELOPMENT (TOD) SYSTEM - Muhammad Fariz; Zahera Mega Utama; Franky (BETRIK, 2024)
This research examines the phenomenon of increasing the number of South SumatraLRT users through a differentiation strategy based on Transit Oriented Development (TOD).Using a qualitative descriptive approach, this research explores the TOD concept implementedby South Sumatra LRT managers in Palembang City. Data was collected through observation,interviews and documentation from January to October 2023. The results of the analysis showthat the implementation of TOD has increased the load factor of the South Sumatra LRT, althoughit still faces several challenges such as overlapping stakeholder interests and a lack of effectivepromotion. This research method involves preliminary observations to understand the context ofthe South Sumatra LRT, followed by field research to obtain more in-depth data. Informants wereselected purposively based on their expertise and relevance to the research topic. Data wereanalyzed through triangulation of sources and theories to ensure the validity of the results. Theresults of the analysis show that the TOD-based differentiation strategy has a positive impact onthe South Sumatra LRT load factor, especially through infrastructure development and effectivepromotion. This research concludes that a TOD-based differentiation strategy can be an effectivemodel for increasing the use of mass transportation services such as the South Sumatra LRT. Byinvolving collaboration between the government and the private sector, as well as improvingfacilities and promotions, the South Sumatra LRT can become a transportation alternative that ismore popular with the public. However, further steps are needed to overcome the challenges stillbeing faced, such as overlapping stakeholder interests and the use of private transportation.